Detection of Silent Atrial Fibrillation aFter Ischemic StrOke (SAFFO) guided by implantable loop recorder: multicentre Italian trial based on stroke unit network with paired cardio-arrhythmology units (Italian Neurocardiology Unit Network). Issue 3 (April 2016) - Toni, Danilo; Lorenzano, Svetlana; Strano, Stefano; ,
Rationale: Atrial fibrillation is associated with a high risk of stroke and its prevalence increases in subjects aged ≥65 years. After an ischemic stroke, the use of standard monitoring methods may underestimate the detection rate of atrial fibrillation. Hence, it is very likely that even patients having a first atherothrombotic or lacunar stroke with high burden of vascular risk factors are exposed to increased risk of developing atrial fibrillation in the subsequent years and atrial fibrillation may be the cause underlying possible recurrent strokes Aim and hypothesis: The Silent Atrial Fibrillation aFter Ischemic StrOke (SAFFO) trial has the objective to evaluate the detection of atrial fibrillation or atrial flutter as first diagnosis by implantable loop recorder in patients with first-ever atherothrombotic or lacunar stroke. We hypothesize that the detection will be higher than that observed by using standard cardiac monitoring Methods and design: SAFFO is a prospective, multicenter, randomized, controlled, open-label trial with blinded assessment of outcome measures. Patients who fulfill inclusion criteria will be randomized to either continuous monitoring using an implantable loop recorder plus standard monitoring (intervention arm) or standard heart rhythm monitoring alone (control arm) with a ratio of 1:1 Study outcomes: The primary endpoint is the detection of atrial fibrillation/atrial flutter as first diagnosis in the first 12 months of the study period Discussion: If positive, SAFFO trial could have important clinical implications in terms of changing the standard diagnostic protocol in patients with atherothrombotic and lacunar stroke, and of increasing the shift of secondary prevention treatment from antiplatelet to anticoagulant therapy.